PENGARUH TANJAKAN DAN VOLUME MUATAN TERHADAP PRODUKTIVITAS LORI DORONG DI HUTAN JATI - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1990)
An  investigation on the effect of slopes and load volumes  on the productivity  of hand lorry was carried out  at Padangan Forest  District, Unit II Perum Perhutani,  East Java, in 1983.  In the investigation,  four  levels of slopes  (i.e. 3, 4, 5, and 6 percent), four  levels of  load volumes  (i.e. 3.5, 4.0, 4.5, and 5.0 m3) and the crew of 4 workers were used.  The objective was to find  the productivity of  hand  lorry  opearating  on several slopes  and  with  several load volumes. The results reveal that:The productivities of log hauling by hand lorry ranged from : 7.16 to 25.09  m3km/hour   with an average of 16.46  m3km/hour.Higher slope and load volume  caused the decrease in lorry productivity.The relation  of productivity (Y), slope (X 1) and load volume (X2) can  be expressed  by  the following  equation  of linear multiple regression: Y  = 48.626 - 2.199X1 -  5.342X2 with  R2 = 0.58Slopes and load volumes  have highly significant  effect  on productivities.